On the Sensitivity of the Devonian Climate to Continental Configuration, Vegetation Cover, Orbital Configuration, CO 2 Concentration, and Insolation. Issue 8 (23rd August 2019) - Brugger, Julia; Hofmann, Matthias; Petri, Stefan; Feulner, Georg
Abstract: During the Devonian (419 to 359 million years ago), life on Earth witnessed decisive evolutionary breakthroughs, most prominently the colonization of land by vascular plants and vertebrates. However, it was also a period of major marine extinctions coinciding with marked changes in climate. The cause of these changes remains unknown, and it is therefore instructive to explore systematically how the Devonian climate responds to changes in boundary conditions. Here we use coupled climate model simulations to investigate separately the influence of changes in continental configuration, vegetation cover, carbon dioxide (CO2 ) concentrations, the solar constant, and orbital parameters on the Devonian climate. The biogeophysical effect of changes in vegetation cover is small, and the cooling due to continental drift is offset by the increasing solar constant. Variations of orbital parameters affect the Devonian climate, with the warmest climate states at high obliquity and high eccentricity. The prevailing mode of decadal to centennial climate variability relates to temperature fluctuations in high northern latitudes which are mediated by coupled oscillations involving sea ice cover, ocean convection, and a regional overturning circulation. The temperature evolution during the Devonian is dominated by the strong decrease in atmospheric CO2 . Albedo changes due to increasing vegetation cover cannot explain the temperature rise found in Late Devonian proxy data. Finally, simulated temperatures are significantly lower than estimates based on oxygen isotope ratios, suggesting a lower δ 18 O ratio of Devonian seawater. Key Points: We investigate the sensitivity of the Devonian climate using a coupled ocean‐atmosphere model The observed cooling is mainly caused by decreasing atmospheric carbon dioxide levels Higher temperatures inferred from proxies suggest different oxygen isotope ratios in the Devonian